The Impact of Personality and Working Environment Towards Job Performance in Educational Institutions - Caroline Ongkowijoyo; Henry Tjendra Santoso (iBuss Management, 2018)
Enhancing the performance of human capital is significant in order to remain competitive in the current economy, hence organizations need to find an effective and efficient ways. The objective of this paper is to find out the impact of personality and working environment towards job performance. Five-factor model is chosen as the personality taxonomy, and the research aims to examine whether five-factor model, which is mediated by self-efficacy, and working environment can affect the job performance of human resources in a few educational institutions.The paper uses simple random sampling, using online questionnaire to gather the data from various educational institutions. The data has passed validity & reliability test, as well as processed using multiple regression with path analysis and Sobel test.The main finding of this research suggests that personality significantly impacts job performance, even more when personality is mediated by self-efficacy. Working environment, on the other hand, impacting job performance less significantly. Furthermore, self-efficacy is found to partially mediate the relationship between five-factor model to job performance. Keywords: Personality, Five-Factor Model, Self-Efficacy, Working Environment, Job Performance